Etude des effectifs et de la repartition saisonniere des elephants des aires classes de l’est du Burkina Faso - Chardonnet, Bertrand (Pachyderm, 2000)
Two aerial surveys of the Arly NP area and Singou River basin, one in February the middle of the dry season and the other in July at the beginning of the rainy season, provided insight into status and distribution of elephants. The population estimate is about 3000 elephant, they were widely distributed with the exception of the eastern or Koakrana area where none were present during either survey. Densities were quite variable with the distributions being wider in the rainy season. The average group size was 6.7 during the dry season and 6.0 in the wet. This number does not seem to pose a problem vis a vis the human population, nor does the vegetation appear degraded. The onset of the rains seemed to be a centripedal movement towards the centre of the areas flown. The only movement towards the outside of the area was in the south where animals crossed the Pendjari River. Approximately two thirds of the numbers are concentrated in the Singou Basin. ( Pama region). The population increase since 1982 averagies about 4.7% per year. Few carcasses were observed, and the number of elephant poached in recent times does not seem to be more than 20.